2020
DOI: 10.1001/jamanetworkopen.2020.15626
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Deep Learning Model to Predict Hepatocellular Carcinoma in Patients With Hepatitis C Cirrhosis

Abstract: Key Points Question Can deep learning recurrent neural network (RNN) models using raw longitudinal data extracted directly from electronic health records outperform conventional regression models in predicting the risk of developing hepatocellular carcinoma (HCC)? Findings This prognostic study included 48 151 patients with hepatitis C virus (HCV)–related cirrhosis in the national Veterans Health Administration who had at least 3 years of follow-up after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 51 publications
0
70
0
Order By: Relevance
“…A deep learning, recurrent neural network model predicting HCC in patients with HCV was recently published. 37…”
Section: "Deep Learning" Hcc Prediction Modelsmentioning
confidence: 99%
“…A deep learning, recurrent neural network model predicting HCC in patients with HCV was recently published. 37…”
Section: "Deep Learning" Hcc Prediction Modelsmentioning
confidence: 99%
“…In particular, SVR patients could be classified as having low or moderate HCC risk according to these simple biological parameters. Similarly, deep learning models were recently applied to data in the VA database [ 49 ]. In this context, use of a recurrent neural network (RNN) outperformed conventional models in identifying patients with the highest HCC risk regardless of their SVR status.…”
Section: Identification Of Patients Infected With Hcv With Higher mentioning
confidence: 99%
“…Traditional analysis depends on expert‐defined phenotyping and ad hoc feature engineering 42 ; however, the generalizability of results is often limited. DL models have been successfully applied to healthcare to predict clinical events, disease classification, and EHR data augmentation, 43 because of the better performance of DL and the capability to analyze complex datasets. The selected applications of AI using EHR are listed in Table 4.…”
Section: Artificial Intelligence In Electronic Health Recordsmentioning
confidence: 99%
“…Inannou et al . used the DL RNN models to analyze raw longitudinal data from EHR and investigated the risk of HCC among 48 151 patients with chronic hepatitis C‐related cirrhosis with at least 3‐year follow‐up 43 . They found that RNN models with longitudinal data (AUROC: 0.759) outperforms logistic regression model using cross‐sectional or longitudinal inputs (AUROC: 0.68–0.69).…”
Section: Artificial Intelligence In Electronic Health Recordsmentioning
confidence: 99%